EFEKTIVITAS PENDEKATAN PROJECT BASED LEARNING DALAM KETERAMPILAN MEMBUAT TAS BATIK BAGI PESERTA DIDIK TUNARUNGU (Pre Experimental Design di Kelas VIII SLB YPPC Painan) - Rahma Wulan Sari; Zulmiyetri Zulmiyetri (Jurnal Penelitian Pendidikan Khusus, 2023)
This take a look at discusses the troubles encountered by way of researchers at SLB YPPC Painan, wherein there are six deaf students in class VIII at SLB YPPC Painan. In schools there's gaining knowledge of approximately the capabilities of recycling used items. The competencies to recycle used goods which have been implemented are making fruit holders from plastic cups, making key chains from bottle caps and making wall hangings from plastic spoons. So, to improve the learning of used goods recycling skills, researchers want to train a new skill that has never been implemented in schools, particularly making batik bags.Â The technique used in this statement is pre-experimental design pretest and posttest. The consequences of the pretest and posttest which have been received are searched for evaluation to test the research hypothesis.Then tested the use of the Mann Whitney U testÂ based totally on the results tested using the Mann Whiteny U test. based on the consequences of information processing, it was acquired that Uhit 36.5 changed into taken from the smallest fee with a importance stage of 95% and 0.05 become obtained Utab 5, in order that Utab Utab then Ha was general and Ho become rejected. From the results of this have a look at it become said that the venture based totally studying approach was correctly used within the competencies of creating batik bags for deaf college students at SLB YPPC Painan.Â